2015
DOI: 10.1002/mc.22256
|View full text |Cite
|
Sign up to set email alerts
|

MiR125a‐5p acting as a novel Gab2 suppressor inhibits invasion of glioma

Abstract: Poor prognosis of glioma is due to the characteristics of high invasiveness. Recently, it was demonstrated that Gab2 was over-expressed and related to cellular migration and invasion in glioma, however, the mechanisms of regulation are still unknown. A better understanding of molecular events key to the carcinogenesis and tumor progression may facilitate development of new therapeutic targets and anti-glioma strategies. This study is the first to focus on miR125a-5p, which was predicted to regulate Gab2 with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 34 publications
(45 reference statements)
4
20
0
Order By: Relevance
“…For tumour suppressor genes, such as miR-125a-5p, the molecules are commonly hypermethylated in tumour tissues compared with non-tumour tissues. In addition to our study here, the miR-125a-5p has been demonstrated to be hypermethylated in glioma cells 27. Target gene screening and validation showed that the histone methyltransferase Suv39H1 was the miR-125a-5p target gene, which Suv39H1 is the miR-125a-5p target gene.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…For tumour suppressor genes, such as miR-125a-5p, the molecules are commonly hypermethylated in tumour tissues compared with non-tumour tissues. In addition to our study here, the miR-125a-5p has been demonstrated to be hypermethylated in glioma cells 27. Target gene screening and validation showed that the histone methyltransferase Suv39H1 was the miR-125a-5p target gene, which Suv39H1 is the miR-125a-5p target gene.…”
supporting
confidence: 64%
“…It has been demonstrated that some epigenetic modulators could modulate the miR‐125‐5p expression, such as HDACs (histone deacetylases),13, 25 or be modulated by miR‐125‐5p, such as Sirtuins 26. Furthermore, the putative promoter regions the miR‐125a‐5p are embedded in CpG islands and are hypermethylated in glioma cells 27. Considering the above findings, we wanted to test the expression and methylation status of miR‐125a‐5p in gastric cancer tissues and adjacent non‐tumour tissues and then to evaluate whether DNA methylation participates in regulating miR‐125a‐5p expression in human gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…*P , 0.05, **P , 0.01. (51,52). In the present study, inhibitors of PI3K, MEK, or Jak2 significantly suppressed Gab2-mediated HepG2 cell proliferation and migration.…”
Section: Discussionsupporting
confidence: 57%
“…Moreover, Gab2 contributes to the angiogenic switch by increasing hypoxia-inducible factor-1α and VEGF levels in melanoma (29). In glioblastoma, both miRNA-197 and miR125a-5p inhibit glioma cell proliferation and invasion by negatively regulating Gab2 (51, 52). In the present study, inhibitors of PI3K, MEK, or Jak2 significantly suppressed Gab2-mediated HepG2 cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…LIM kinase 1 (LIMK) is involved in the regulation of F-actin polymerization [11, 12]. F-actin dynamics is also regulated by the phosphorylating cofilin at Ser3, which is critical for cell chemotaxis and migration [13, 14]. Analysis of PlGF-1-induced phosphorylation of LIMK and cofilin in MDA231/miR-507 cells showed a marked inhibit activation of both cofilin and LIMK, compared with MDA231/NC cells, whereas both total LIMK and cofilin levels remained unchanged (Figure 3F).…”
Section: Resultsmentioning
confidence: 99%